Electrochemical Estimations of the Gold Nanoparticle Size Effect on Cysteine-Gold Oxidation. Issue 2 (4th February 2022) - Romanovskaia, Elena; Slovenský, Peter; Kalantarian, S. Marzieh; Laundry-Mottiar, Lila; Romanovski, Valentin; Halama, Maroš; Auinger, Michael; Hedberg, Yolanda S.
Abstract : Gold nanoparticles are interesting for nanobiomedical applications, such as for drug delivery and as diagnostic imaging contrast agents. However, their stability and reactivity in-vivo are influenced by their surface properties and size. Here, we investigate the electrochemical oxidation of differently sized citrate-coated gold nanoparticles in the presence and absence of L-cysteine, a thiol-containing amino acid with high binding affinity to gold. We found that smaller sized (5, 10 nm) gold nanoparticles were significantly more susceptible to electrochemical L-cysteine interactions and/or L-cysteine-facilitated gold oxidation than larger (20, 50 nm) sized gold nanoparticles, both for the same mass and nominal surface area, under the conditions investigated (pH 7.4, room temperature, stagnant solutions, and scan rates of 0.5 to 450 mV s −1 ). The electrochemical measurements of drop-casted gold nanoparticle suspensions on paraffin-impregnated graphite electrodes were susceptible to the quality of the electrode. Increased cycling resulted in irreversible oxidation and detachment/oxidation of gold into solution. Our results suggest that L-cysteine-gold interactions are stronger for smaller nanoparticles.